2020
DOI: 10.1016/j.immuni.2019.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Targeting 7-Dehydrocholesterol Reductase Integrates Cholesterol Metabolism and IRF3 Activation to Eliminate Infection

Abstract: Highlights d Multiple infections reduce DHCR7 expression but increase AKT3 expression in macrophages d DHCR7 deficiency and 7-DHC treatment activate the PI3K-AKT3 pathway d AKT3 binds IRF3 to enhance IRF3 Ser385 phosphorylation needed for full IRF3 activation d Targeting DHCR7 protects mice from various viral infections

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 51 publications
2
102
0
Order By: Relevance
“…DHCR7 is downregulated during RNA virus infection in macrophages to promote IRF3 signaling and IFN-1 production. Moreover, inhibition of DHCR7 aids in clearance of multiple RNA viruses 47 . These previous findings indicate that interactions with IDI1 and DHCR7 may provide means for coronaviruses to counteract anti-viral responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DHCR7 is downregulated during RNA virus infection in macrophages to promote IRF3 signaling and IFN-1 production. Moreover, inhibition of DHCR7 aids in clearance of multiple RNA viruses 47 . These previous findings indicate that interactions with IDI1 and DHCR7 may provide means for coronaviruses to counteract anti-viral responses.…”
Section: Discussionmentioning
confidence: 99%
“…We observed shared interactors between OC43 and SARS-CoV-2, such as the Nglycosylation factor RFT1 39,40 and a sarcoplasmic/endoplasmic reticulum calcium ATPase (SERCA -ATP2A2) 41 . In addition, we identified shared interactors between OC43 and SARS-CoV-1, including a regulator of UPR-mediated apoptosis (WLS or GPR177) 42 , a member of the signal peptidase complex (SEC11A) 43 , and factors involved in cholesterol synthesis (IDI1, DHCR7) [44][45][46][47] . WLS, SEC11A, and DHRC7 exhibited higher enrichment for OC43, whereas IDI1 was more greatly enriched for SARS-CoV-1.…”
Section: Analysis Of Go-mentioning
confidence: 99%
“…7-DHC is the direct precursor of free cholesterol and the substrate of 7-dehydrocholesterol reductase (DHCR7). Xiao et al (2020) found significantly increased DHCR7 expression in livers of hepatocellular carcinoma (HCC) patients with HBV infection. 7-DHC was also a biosynthesis precursor to vitamin D, thus increased DHCR7 promoted cholesterol synthesis while inhibited Vitamin D production (Prabhu et al, 2016).…”
Section: Hbv-induced Changes In Cholesterol Metabolismmentioning
confidence: 97%
“…Furthermore, SC5D regulates the enzyme converting lathosterol to 7-Dehydrocholesterol. And the downstream gene DHCR7, which converts 7-Dehydrocholesterol to cholesterol, has been targeted by drugs inhibiting HBV infection (Xiao et al, 2020). Therefore, although the three genes are currently not targets of existing drugs, they are all related to the main-effect pathway cholesterol biosynthesis and important for tumorigenesis of HCC.…”
Section: Metabolic Genes In Cholesterol Biosynthesis Are Druggable Tamentioning
confidence: 99%